Perception of Early Internationalization and Its Determinants by Managers of New-Technology Based Firms - Dorota SOBOL (Communications of International Proceedings, 2021)
Over the years, the perception of internationalization by both theoreticians and practitioners has clearly changed. This important strategic decision concerns many modern enterprises, and some of them - despite many limitations - implement this goal in the first years of operation. At present, attempts are being made to identify and verify the factors involved in the early internationalization of a particular group of new-technology based firms (NTBF) from small, open and emerging economies. The aim of this article was to identify the current stage of NTBF internationalization and the perception of determinants of early internationalization by managers of these companies. To achieve this goal, the latest research results were reviewed, and then an own survey was conducted using the survey method among the management staff of new-technology based firms operating in science and technology parks (STP) in one voivodeship in Poland. As the research shows, managers treat internationalization as a natural path of development inscribed in the strategic goals of the company or as an opportunity, and no one as "redundant activity". Most of the entities internationalized their activities within 5 years from the year they started their operations, choosing simple active forms of expansion. Moreover, the respondents declare their willingness to maintain or expand their foreign activity in the next few years. On the basis of the obtained results, it was also possible to create a ranking list of key factors of early internationalization of these companies. In addition, the elements of the STP offer dedicated to tenant enterprises that are worth improving to support their preparations for internationalization have been noted. The directions of future research were also indicated.
Keywords: Early Internationalization; Determinants; New-Technology Based Firms.